RANCANG BANGUN ALAT UKUR FLEKSIBILITAS TUBUH MENGGUNAKAN SENSOR JARAK BERBASIS MIKROKONTROLER - Roynald Natan Nugrawan, Tan Suryani Sollu, Nurhani Amin (Foristek, 2019)
Body flexibility is one of the factors that greatly helps physical health because it can help in prevention, help restore muscle, and improve efficiency in various physical activities. One method to measure the body speed level is Sit and Reach Test using the Sit and Reach Box Scale measurement tool. Technically, this measuring instrument is still manual, simple and its production is still very limited. Therefore we need a measuring device to use electronic components to help process better and better in terms of which can be adjusted to good or bad by using the parameter norm Sit and Reach Test. The purpose of this study is to design a flexibility measuring instrument using a microcontroller based proximity sensor. This tool works with the arduino unu microcontroller as the main controller, HC-SR04 ultrasonic sensor as a distance reader for body flexibility, LED indicators and speakers as a sign of body flexibility, then LCD and delphi 7 applications using serial communication as a display of body flexibility.